Theoretical evaluation of the carbene-based site-selectivity in gold(iii)-catalyzed annulations of alkynes with anthranils. Issue 12 (14th January 2021) - Wang, Kaifeng; Wu, Qiao; Bi, Siwei; Liu, Lingjun; Chen, Guang; Li, Yulin; James, Tony D.; Liu, Yuxia
Abstract : The mechanisms and origins of multiple-site selectivities of versatile gold(iii )-catalyzed annulations of alkynes with anthranils are theoretically unraveled. Abstract : The gold(iii )-catalyzed annulations of alkynes with anthranils were evaluated using DFT calculations. A unified rationale for the Br-migration on α-imino gold(iii )-carbene was proposed, from which an unprecedented "N-donation/abstraction substitution" mechanism was established using the substituted anthranils, while direct C–H nucleophilic attack was involved with the unsubstituted anthranils. The controlling factors guiding the site-selectivity were uncovered. These computational studies provide insight for developing new α-imino gold(iii )-carbene mediated reactions.